2007
DOI: 10.1007/s10461-007-9223-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Attitudinal and Relationship Predictors of Sexual Risk in the Multicenter AIDS Cohort Study

Abstract: We examined the influence of attitudes concerning HIV transmission, safe sex, and sexual sensation seeking, as well as negotiated risk reduction with primary partners, on the proportion of unprotected sexual partners (%UASP) among men who have sex with men (MSM). Participants were 263 HIV-seropositive and 238 HIV-seronegative MSM in the Multicenter AIDS Cohort Study between 1999 and 2003 who completed a 20-item attitude survey twice. Behavioral data were collected concurrently and 6-12 months after each survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
2
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 31 publications
6
48
2
3
Order By: Relevance
“…While the intent may be to practice safer sex on a consistent basis, this behavior may not always occur, particularly since the lifelong commitment to condom use may be challenged by ''safe sex fatigue'' over time. 6 Furthermore, HIV serostatus disclosure to sexual partners does not guarantee engagement in protective behaviors to avoid transmission. In our sample, more than 20% of participants followed this disclosure/sexual behavior pattern termed ''informed exposure.''…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the intent may be to practice safer sex on a consistent basis, this behavior may not always occur, particularly since the lifelong commitment to condom use may be challenged by ''safe sex fatigue'' over time. 6 Furthermore, HIV serostatus disclosure to sexual partners does not guarantee engagement in protective behaviors to avoid transmission. In our sample, more than 20% of participants followed this disclosure/sexual behavior pattern termed ''informed exposure.''…”
Section: Discussionmentioning
confidence: 99%
“…Although being diagnosed with HIV has been associated with a significant reduction in sexual risk behavior, 1-3 a substantial minority of PLHIV continue to engage in unprotected sex. [4][5][6][7] Others may decrease sexual risk behavior immediately after diagnosis but show a rebound in these behaviors in subsequent months or years. For example, one study of men who have sex with men (MSM) who were recently infected with HIV found that the percentage of unprotected sex with unknown serostatus partners decreased from 49% at baseline to 25% at 6 months, but then rebounded to 71% at 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…During the course of the HIV epidemic, phenomena such as safe sex fatigue and treatment optimism adversely impacted risk reduction messages of public health campaigns and led to an attitude of indifference with regard to safety among some gay men (Ostrow et al, 2008;Schwarcz et al, 2007). MSM also developed a number of strategies that may or may not be effective in reducing the chances of becoming infected while opting not to use condoms with their partners.…”
Section: Discussionmentioning
confidence: 99%
“…1 The disparate impact of HIV and other STIs on MSM as compared to heterosexual men and women reflects both biological [3][4][5] and behavioral 4,6,7 factors. High levels of HIV risk behavior among MSM, and the resurgence of the HIV epidemic in this population, 8 may also be the result of several psychosocial factors, including the changed perception of HIV as a chronic and manageable rather than terminal illness, 9 lack of awareness of HIV status, 10 substance abuse, 11 increased access to and use of testing, 12 condom fatigue, 13 and use of harm reduction techniques including serosorting.…”
mentioning
confidence: 99%